Fuzzy Logic Controller for grid connected Wind Energy Conversion System - G. Muni Reddy; T. Gowri Manohar (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2018)
The use of renewable power sources, like wind power, has been increased recently due to climatic changes caused by fossil fuels and fast depletion of fossil fuels. This has lead to the tremendous increase in the interconnection of wind turbines to power system grid. This interconnection on a large number in to grid causes problems such as power quality, maintaining system voltage, reactive power compensation, control of grid frequency and aspects of power system grid stability. In this proposed scheme, a fuzzy logic based controller is employed for a STATCOM to improve the power quality. The proposed control scheme supplies the required reactive power to the system and thus relieves the source, leading to Unity Power Factor (UPF) at the source and also it injects currents to reduce total harmonic distortion (THD) to satisfy IEC standard. For extracting the reference currents, an instantaneous reactive power theory based control algorithm is employed. To determine the effectiveness of the proposed fuzzy logic controller, a comparative analysis is also performed with a PI controller and the results have been presented.